2023
DOI: 10.1038/s43705-023-00249-1
|View full text |Cite
|
Sign up to set email alerts
|

The association of prokaryotic antiviral systems and symbiotic phage communities in drinking water microbiomes

Abstract: Prokaryotic antiviral systems are important mediators for prokaryote-phage interactions, which have significant implications for the survival of prokaryotic community. However, the prokaryotic antiviral systems under environmental stress are poorly understood, limiting the understanding of microbial adaptability. Here, we systematically investigated the profile of the prokaryotic antiviral systems at the community level and prokaryote-phage interactions in the drinking water microbiome. Chlorine disinfectant w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…A recent pangenome analysis has unveiled various new systems within bact nomes, some of which elucidate novel defense mechanisms at the population le These bacterial defense systems pose challenges to the effectiveness of phage app The thorough characterization of phage defense systems, along with their potentia backs, is essential for the deeper comprehension of the hurdles in practical phag cation and for the advancement of phage technology. Of the 151 antiphage systems today, 24 were found in the investigated Leptospira strains (Figure 5) [28].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent pangenome analysis has unveiled various new systems within bact nomes, some of which elucidate novel defense mechanisms at the population le These bacterial defense systems pose challenges to the effectiveness of phage app The thorough characterization of phage defense systems, along with their potentia backs, is essential for the deeper comprehension of the hurdles in practical phag cation and for the advancement of phage technology. Of the 151 antiphage systems today, 24 were found in the investigated Leptospira strains (Figure 5) [28].…”
Section: Discussionmentioning
confidence: 99%
“…The thorough characterization of phage defense systems, along with their potential drawbacks, is essential for the deeper comprehension of the hurdles in practical phage application and for the advancement of phage technology. Of the 151 antiphage systems known today, 24 were found in the investigated Leptospira strains (Figure 5) [28]. The functional subunits of R-M systems include methyltransferase (MTas transfers a methyl group from the S-adenosyl methionine (SAM) donor molecul sine or adenine in the DNA, along with the corresponding restriction endo (REase).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Six phages (ctg182745, ctg307755, ctg321052, ctg328091, ctg409955, and ctg98054) were found to possess gene DNMT1 encoding DNA (cytosine-5)-methyltransferase 1 (EC:2.1.1.37), which was involved in organic nitrogen metabolism (cysteine and methionine metabolism). The gene DNMT1 was also detected in phage genomes in drinking water distribution systems (Huang et al, 2023). In addition, one contig (ctg409955) was found to carry the gene asnB (Figure 4B), which is also associated with organic nitrogen metabolism.…”
Section: Potential Functions Of the Phage Communitymentioning
confidence: 94%
“…For instance, studies have shown enrichment of functional traits (e.g., necrotrophy) in a treatment and disinfection strategy-specific manner [13][14][15][16] . Metagenomics has also helped identify pathogenic traits 15 and antibiotic resistant genes 17,18 and further elucidated the prevalence of phages 4 and anti-phage defense mechanisms 19 which can impact microbial community dynamics. Recently, Liu et al (2024) 15 conducted a meta-analysis involving reconstruction and consolidation of metagenome assembled genomes (MAGs) from multiple drinking water metagenomes.…”
Section: Introductionmentioning
confidence: 99%